Materials science and engineering of carbon : fundamentals - Inagaki, Michio (Butterworth-Heinemann, 2014)
Annotation Materials Science and Engineering of Carbon: Fundamentals provides a comprehensive introduction to carbon, the fourth most abundant element in the universe. The contents are organized into two main parts. Following a brief introduction on the history of carbon materials, Part 1 focuses on the fundamental science on the preparation and characterization of various carbon materials, and Part 2 concentrates on their engineering and applications, including hot areas like energy storage and environmental remediation. The book also includes up-to-date advanced information on such newer carbon-based materials as carbon nanotubes and nanofibers, fullerenes and graphenes. Through review on fundamental science, engineering and applications of carbon materials. Overview on a wide variety of carbon materials (diamond, graphite, fullerene, carbon nanotubes, graphene, etc.) based on structure and nanotexture. Description on the preparation and applications of various carbon materials, in the relation to their basic structure and properties.
Keywords: Materials science.; Carbon compounds.; elektronické knihy; electronic books